2003
DOI: 10.1080/01926230390226645
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage in Nasal and Brain Tissues of Canines Exposed to Air Pollutants Is Associated with Evidence of Chronic Brain Inflammation and Neurodegeneration

Abstract: Acute, subchronic, or chronic exposures to particulate matter (PM) and pollutant gases affect people in urban areas and those exposed to fires, disasters, and wars. Respiratory tract inflammation, production of mediators of inflammation capable of reaching the brain, systemic circulation of PM, and disruption of the nasal respiratory and olfactory barriers are likely in these populations. DNA damage is crucial in aging and in age-associated diseases such as Alzheimer's disease. We evaluated apurinic/apyrimidin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 292 publications
(125 citation statements)
references
References 113 publications
6
105
0
2
Order By: Relevance
“…Those particles of nanoscale dimensions, requiring analysis by transmission rather than scanning electron microscopy, have, until recently, received less attention than the larger, often more heterogenous spherules. Magnetite nanospheres up to ≾ 200 nm can have a direct entry route to the brain through the axons of the olfactory nerve, as suggested by experimental studies on carbon (29) and TiO 2 nanoparticles (30), and the reported presence of NPs in the olfactory bulb of some Mexico City cases (14,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 92%
“…Those particles of nanoscale dimensions, requiring analysis by transmission rather than scanning electron microscopy, have, until recently, received less attention than the larger, often more heterogenous spherules. Magnetite nanospheres up to ≾ 200 nm can have a direct entry route to the brain through the axons of the olfactory nerve, as suggested by experimental studies on carbon (29) and TiO 2 nanoparticles (30), and the reported presence of NPs in the olfactory bulb of some Mexico City cases (14,(31)(32)(33).…”
Section: Discussionmentioning
confidence: 92%
“…We selected COX2 mRNA levels as the primary variable because of the striking upregulation of COX2 expression observed in the brains of dogs residing in Mexico City (Calderón-Garcidueñas et al, 2003a) and because enhanced neuronal COX2 expression in hippocampus is a feature of the clinical progression of early Alzheimer's disease (Ho et al, 2001). COX2 mRNA abundance was measured by real-time RT-PCR analysis of total RNA isolated from frontal cortex and hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative analysis of COX2 and Aβ42 was performed with the BioQuant Nova prime image analysis system (Bioquant Image Analysis Corp, Nashville, TN). To quantify the number of AP sites we used an aldehyde reactive probe (ARP) (Calderón-Garcidueñas et al, 2003a). AP sites are expressed per 1 × 10 6 nucleotides.…”
Section: Autopsy and Tissue Preparationmentioning
confidence: 99%
See 2 more Smart Citations